Uncovering Self-Identity of Adolescent Students - Fitra, Adi; Syukur, Yarmis; Asfina, Risda (Suluh: Jurnal Bimbingan dan Konseling, 2023)
Adolescence is a period of transition from children to adults. Transitional status often makes adolescent students confused in determining which choices are right for themselves. In fact, they need to know themselves better, their potential and what they like and dislike, and to make plans for their future. Therefore, to avoid confusion in their selves, self-identity is needed. The purpose of this study is to describe aspects of self-identity of adolescent students at SMA Negeri 4 Padang. The data were collected through a self-identity questionnaire given to a total of 33 students. This study used purposive sampling technique. The data were analyzed quantitatively and described comprehensively. This study found that the mean score of adolescent students’ self-identity was 133.52 or 72.07% of the ideal score. In addition, 9.09% students had very high self-identity; 36.36% students had high self-identity; 24.24 students had moderate self-identity; 30.30 students had low self-identity; and none had very low self-identity. The development of self-identity of adolescent students must continue to be improved in order to support the development of their learning.